Key performance indicators of private finance initiative (PFI) projects during pre-construction phase - Ismail, Suhaiza; Mohamad, Rosnani; Mohd Said, Julia (Faculty of Built Environment, UM, 2024)
There are two objectives of this paper. The first objective is to investigate the important performance indicators of private finance initiative (PFI) or also known as public private partnership (PPP) projects before beginning of construction. The second objective is to investigate the difference in the perception of the importance of the performance indicators between the public and private sectors. A postal questionnaire survey was used. The questionnaire was distributed officers of government departments and private sector companies who may have been involved in PFI/PPP projects. A total of 237 completed questionnaires were received, representing a 51.52 percent response rate. In examining the importance of performance indicators, the descriptive statistical tests of mean, standard deviation and mean score ranking were used. Independent t-tests were conducted to investigate the differences in the perceptions of the importance of performance indicators between the two respondent groups. The findings indicate that all the performance indicators in relation to before the construction period were perceived as ‘important’ by all respondents. The top five performance indicators before construction begins were ‘Project maintainability’, ‘Commitment and responsibility between public and private sectors’, ‘Government’s knowledge of PFI/PPP’, ‘Project technical feasibility’ and ‘Appropriate risk allocation, risk sharing and risk transfer’. The performance indicator that was perceived as the least important was ‘Stable and favourable political environment’. In terms of the differences in the opinion between the private sector and the public sector respondents, two indicators that are ‘General public support’ and ‘Type of construction’ were perceived by the public sector respondents as significantly more important than by the private sector respondents. This study offers empirical evidence on key performance indicators for PFI/PPP project that are important at the early yet crucial stage of a PFI/PPP contract, i.e. before construction begins, as perceived by two key parties in a PFI/PPP contract, i.e., the public and the private sectors.